2015
DOI: 10.1104/pp.115.256834
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxide-Derived Short-Chain Carbonyls Mediate Hydrogen Peroxide-Induced and Salt-Induced Programmed Cell Death in Plants  

Abstract: Lipid peroxide-derived toxic carbonyl compounds (oxylipin carbonyls), produced downstream of reactive oxygen species (ROS), were recently revealed to mediate abiotic stress-induced damage of plants. Here, we investigated how oxylipin carbonyls cause cell death. When tobacco (Nicotiana tabacum) Bright Yellow-2 (BY-2) cells were exposed to hydrogen peroxide, several species of short-chain oxylipin carbonyls [i.e. 4-hydroxy-(E)-2-nonenal and acrolein] accumulated and the cells underwent programmed cell death (PCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
122
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 65 publications
4
122
0
1
Order By: Relevance
“…Therefore, lipid-derived RCS also could affect various molecular targets, which were not examined in this study in plant cells because of their reactivities, and aor mutants might cause the decrease of carbon utilization during the night and the growth retardation as a result of the modification of plant cell components. Moreover, lipid-derived RCS have been reported to be involved in signaling processes such as auxin signaling and cell division (Farmer and Mueller, 2013;Biswas and Mano, 2015;Yamauchi et al, 2015). Based on these reports, lipid-derived RCS diffused in plant cells might modify the gene expression network, which is not analyzed in this study, and cause the decrease of carbon utilization during the night and the growth retardation in aor mutants.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, lipid-derived RCS also could affect various molecular targets, which were not examined in this study in plant cells because of their reactivities, and aor mutants might cause the decrease of carbon utilization during the night and the growth retardation as a result of the modification of plant cell components. Moreover, lipid-derived RCS have been reported to be involved in signaling processes such as auxin signaling and cell division (Farmer and Mueller, 2013;Biswas and Mano, 2015;Yamauchi et al, 2015). Based on these reports, lipid-derived RCS diffused in plant cells might modify the gene expression network, which is not analyzed in this study, and cause the decrease of carbon utilization during the night and the growth retardation in aor mutants.…”
Section: Discussionmentioning
confidence: 87%
“…Combining the results of Mano et al (2014a) and our study, we concluded that chloroplasts are a major production site of lipid-derived RCS and might be an initiator for lipidderived RCS-dependent signaling cascades in plant cells. Accordingly, further intensive studies are required to elucidate the molecular targets of lipidderived RCS, especially the receptors of lipid-derived RCS triggering the signal cascade in plant cells (Farmer and Mueller, 2013;Biswas and Mano, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is an increasing body of evidence for the generation of toxic levels of aldehyde in response to environmental stresses, especially lipid peroxidation-derived reactive carbonyl species (RCS) such as malondialdehyde (MDA), acrolein, and 4-hydroxyl-2-nonenal (HNE; Mano, 2012, Biswas andMano, 2015). The detoxification of aldehydes by plant AAO4 or by other AAO family members has never been shown.…”
mentioning
confidence: 99%
“…Aldehydes can be extremely toxic when produced in excess because of their inherent chemical reactivity (Bartels, 2001;Kotchoni et al, 2006;Zhang et al, 2012;Biswas and Mano, 2015). These toxic compounds also may lead to lipid peroxidation and reactive oxygen species (ROS) enhancement (Lamb and Dixon, 1997;Bolwell, 1999) to levels that could damage biomolecules such as proteins, lipids, carbohydrates, and DNA, which, in extreme cases, can lead to plant death (Gratao et al, 2005, for review, see Gill and Tuteja, 2010;Mano, 2012).…”
mentioning
confidence: 99%